Polling station operation : manual of instructions for polling day staff (Trinidad and Tobago. Elections and Boundaries Commission Port of SpainTT, 2005)
Provides instructions for polling day staff for the conduct of general elections in Trinidad and Tobago.
Keywords: ELECTIONS